Public Interest in Plant Variety Protection: A Comparative Study of Compulsory Licensing in Indonesia and India for Food Security - Devi Andani; Sudiyana; R. Murjiyanto; Nita Ariyani; Mohd Zamre Mohd Zahir (Universitas Negeri Semarang, 2025)
This research aims to analyze and compare the legal frameworks of compulsory licensing in the Plant Variety Protection systems of Indonesia and India in accommodating public interest parameters and to analyze the granting of compulsory licenses for public interest in supporting food sovereignty and security in Indonesia. This research uses a normative juridical method with comparative and statutory approaches. The study utilizes secondary data, including primary and secondary legal sources, analyzed qualitatively to examine the regulatory differences in compulsory licensing regimes between Indonesian and Indian jurisdictions. The results of this research are: First, The findings indicate that India possesses a more comprehensive legal framework through the PPVFR Act, which explicitly integrates farmers' rights as a core element of public interest. In contrast, Indonesia's regulations remain administratively centered with an ambiguous definition of “public interest”. A fundamental difference lies in the activation procedures: India allows for swifter intervention against seed monopolies to ensure price stability, whereas in Indonesia, the mechanism is not yet optimally implemented due to a lack of technical implementing regulations capable of responding effectively to food crises. Second, the results indicate that while compulsory licensing is legally accommodated within Indonesia’s PVP system as a public interest instrument, its implementation remains suboptimal in supporting food sovereignty. Consequently, compulsory licensing remains passive, prioritizing the protection of breeders' exclusive rights over its strategic role in ensuring seed accessibility for smallholder farmers.